STUDI HABITAT PENELURAN PENYU HIJAU (Chelonia mydas) DI PANTAI PANGUMBAHAN SUKABUMI JAWA BARAT - Bara, Duduh Abdul; Redjeki, Sri; Hariadi, Hariadi (Departemen Ilmu Kelautan, Fakultas PerikanJurusan Ilmu Kelautan, Universitas Diponegoro)
All sorts of turtle have registered in the list of Apendik I CITES (Convention on International Trade of Endangered Spesies). The convention forbid the international trade of all products/result of turtle: neither the egg, meat or caravas.The purpose of this research is to know the nesting of Green Turtle (Chelonia mydas) reviewed from the physical aspect and biology of Pangumbahan Beach, Sukabumi , West Java. The research was did on January 5th-7th 2011. The method that used is Descriptive Exploratory Method. The research material that used is Green Turtle (Chelonia mydas), the nesting of turtle that include the outside vegetation, predator, the long and wide of beach, the temperature, the slope of beach, the moisture of substrate, and the composition of sand. There is 6 station based on Association of The Green Turtle Cultivation. Data collection was did by direct observation in locates. Based on the research result, the Green turtle (Chelonia mydas) in Pangumbahan Beach achieve 19. The width of Pangumbahan Beach is about 72 - 92 m and the length is about 3000 m. The slope of the beach is about 2.4% - 2.8%. The measured result of the sand temperature is about 28 ËšC - 29.3 ËšC. The composition moisture of surface sediments is about 0.05% - 1.13%, and the moisture inside sediments (50cm) about 0.26% - 4.1%. The sand particle of Pangumbahan Beach is dominated by the medium sand with percentage in each more than 25%. The vegetation that dominate is Pandanus (Pandanus tectorius), meanwhile kind of predators that find in the locate are Wild Dogs (Canis lupus), Red Ants (Oechophylla smaragdina), Crab (Ocypoda sp).